Acquisition of prenominal adjective order by Jordanian EFL learners - Emad Mohammad Al-Saidat; Fatima A. Al-Shalabi; Faten H. Amer (Cakrawala Pendidikan: Jurnal Ilmiah Pendidikan)
This study investigates how Jordanian EFL learners manage to learn the order of English prenominal adjectives, shedding light on learners’ cognitive processes and the possible impact of their first language. It focuses on two-, three- and four-adjective sequences to identify the areas of difficulty and their sources. The authors of the present study relied on their experience. They referred to some experts in Arabic grammar to compare the students’ order of English prenominal adjectives with the order of Arabic adjectives to inform the degree of their mother tongue's influence. A test based on the order of prenominal adjectives suggested by Svatko (1979) was used for data collection to achieve the study objectives. The study participants were 42 Jordanian advanced EFL undergraduate students at Al-Hussein Bin Talal University in Jordan. The study results revealed that Jordanian EFL learners encounter great difficulties in using prenominal adjectives, especially as the complexity of sequences increases. The overall percentage of correct answers across all categories is 35%. The results also showed that intralingual errors outweighed interlingual errors, scoring 77%.